Ethnobotany of Medicinal Plants in the Sumber Harum Village Community, South Sumatra - Evan Andesmora (Universitas Tidar, 2024)
This study describes the potential of plants and the culture of the people in Sumber Harum Village, utilizing medicinal plants around them, which shows the interaction of the community with medicinal plants. Data and information about traditional medicinal plants in Sumber Harum Village and how to use them have yet to be available and documented, especially regarding cultivated and wild medicinal plants. The purpose of this study is to identify the types of traditional medicinal plants, how plants are used by the Sumber Harum Village Community, and analyze community knowledge related to medicinal plants. The research method used is descriptive quantitative, with observation techniques, semi-structured interviews, questionnaires, documentation, collection of plant samples and identification of medicinal plants. Data were analyzed using the Local User's Value Index (LUVI). The research results found that there are 93 species of medicinal plants in Sumber Harum Village, consisting of 75 species of cultivated medicinal plants and 18 species of wild medicinal plants, each of which is grouped into 50 families. The way of utilizing medicinal plants is by boiling them, consuming them directly, pounding them, grating them, squeezing them, and pasting them. The LUVI value of medicinal plants has two categories; the highest value in the cultivation category is avocado leaves (Persea Americana P.Mill) with a value of 0.0689, while the highest type of plant in the wild medicinal plant category is ciplukan (Physalis angulate L.) with a value of 0.0033.